Comparison of the effect of the alcoholic extract of leaves and fruits of hawthorn plant Crataegus azarolus with the drug simvastatin in its effect in reducing cardiovascular disease in male rabbits with experimental fat disorder - Muhanned H. Mukhlif Al-Obaidy; Saleh M.Rahim Al-Obaidy (Tikrit Journal of Pure Science, 2018)
This study designed to investigate the role of both Ethanolic extracts of hawthorn leaves and fruits in reducing cardiovascular risk factors in male  with experimental lipid disorders. 50 male rabbits of New Zealand, 1250-1500g and 8-10 months old used in this study. Rabbits divided into 10 groups (each group 5 male rabbits). The (I) group as a control group, which given the free standard diet and water. The (II) group given high cholesterol (260 mg/Kg) of the weight as a standard diet, the (III) group, which given high cholesterol diet with extracts of C.azarolus (200 mg/kg) of body weight, the (IV) group  which given high cholesterol diet with hawthorn fruit extract (20 mg/kg) Of the body weight, the the (V) group, which was given high cholesterol diet of  body weight, the (VI) group, which given high cholesterol diet with vitamin C (100 mg / kg) of body weight, group (VII), which is the drug of simvastatin, group (VIII), which given vitamin C, the(IX) group given  Hawthorn leaf extract, the (X) group, which given extracts fruit of hawthorn plant. The experiment conducted for six weeks. Statistical analysis showed a significant increase (P<0.05) in the lipid profile variables (total cholesterol, triglyceride, LDL, VLDL and HDL) in the serum and liver extract in the high cholesterol group compared with the control group. Fruits play a more effective role in the prevention of hyperlipidemia compared with vitamin C and the drug of simvastatin and leaf extract. The study also showed a significant decrease (P< 0.05) in the effectiveness of HMG-CoA reductase (HMGR) in the group treated with the drug Simvastatin compared with the control group, while there were no significant differences in the group which given high cholesterol , vitamin C group , extracts of leaves and fruits of the plant group. The conclusion, have found that ethanolic extracts of C. azarolus Low levels of lipids (cholesterol and triglycerides) in the serum of animals experiment with the use of the drug Simvastatin and the fruits of hawthorn plant the largest role compared with vitamin C and extract leaf hawthorn. On the other hand, the non-change in the concentration of the enzyme HMG-CoA reductase in the serum and liver extract indicates that the role of the extract in the normalization of lipid variables is centered on other mechanisms related to the digestive system, such as absorption